2019
DOI: 10.1111/1748-8583.12253
|View full text |Cite
|
Sign up to set email alerts
|

Telling and selling the value of diversity and inclusion—External consultants' discursive strategies and practices

Abstract: Based on a qualitative study of a sub-group of diversity professionals, external diversity and inclusion (D&I) consultants, we explore D&I consultants' discursive strategies and practices situated within organisational structures, relations and interactions of power and knowledge.Theoretically, the research reveals how D&I consultants' own discursive strategies interact with existing organizational and societal discourses of diversity, incrementally shaping their continual evolution. A classification is develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Studying managers of HRM departments, Magoshi and Chang (2009) revealed that organizations try to maintain and manage diversity in the workforce in various ways that interface with other parts of the organization. It is extremely unlikely that DM practices that do not involve employees and actors (Kirton & Greene, 2019) outside the HRM departments will be effective. It is important to include employees from other departments in order to understand practices of DM across the organization (see Edgar & Geare, 2009; Khilji & Wang, 2006), so that practices can be developed in an effective way (Alfes, Truss, Soane, Rees, & Gatenby, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studying managers of HRM departments, Magoshi and Chang (2009) revealed that organizations try to maintain and manage diversity in the workforce in various ways that interface with other parts of the organization. It is extremely unlikely that DM practices that do not involve employees and actors (Kirton & Greene, 2019) outside the HRM departments will be effective. It is important to include employees from other departments in order to understand practices of DM across the organization (see Edgar & Geare, 2009; Khilji & Wang, 2006), so that practices can be developed in an effective way (Alfes, Truss, Soane, Rees, & Gatenby, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Such an appreciation has highlighted the significance of extra‐ and intra‐organizational diversity actors and HRM specialists. For example, Kirton and Greene (2019) demonstrate that HRM specialists need to work with external diversity consultants and actors in order to capture the market and political conditions that give meaning and legitimacy to diversity interventions in their organizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has illustrated the curious discursive transition from the rhetoric of equal opportunities to diversity management to organisational inclusion, suggesting that these changes have been a product of evolving social ideologies and forces (Nkomo and Hoobler, 2014; Oswick and Noon, 2014). Diversity rhetoric that has gradually come to replace the equal opportunities rhetoric and approaches has been critiqued for shifting diversity and equality from a political anti-discrimination project to become a business case underpinned by economic arguments (see Kirton and Greene, 2019; Köllen, 2019). The wealth of recent critical diversity studies contributions has highlighted a range of flaws and issues with both the concept, meaning and practices of managing diversity (see e.g.…”
Section: Conceptualising and Approaching Inclusion In Organisations Cmentioning
confidence: 99%
“…Ahmed (2012) also shows how rhetorical diversity commitments are often used strategically in and by organisations to create a good organisational image, even without much substance to the rhetoric (see also Ashley, 2010). Other research has shown that a range of actors, including diversity consultants and practitioner-facing academics are key to the process of shaping, legitimating and perpetuating certain fads and discursive fashions in diversity management, which are not always supporting but sometimes undermining change for the better (see Healy et al, 2010; Kirton and Greene, 2019; Oswick and Noon, 2014).…”
Section: Doing Inclusion In Organisationsmentioning
confidence: 99%